Dermatological disorders during pregnancy: a study from tertiary care hospital - Patel, Krina B.; Patel, Ruchin; Sharma, Nisha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Various types of physiological and pathological mucocutaneous changes are commonly observed during pregnancy. Infectious, non-infectious and pregnancy specific dermatoses are seen during pregnancy. This study was carried out with an aim of studying association of various dermatosis with pregnancy and to find out incidence of pregnancy specific dermatoses v/s non-specific dermatosis. Methods: Total 131 pregnant female presenting with complain of skin lesions were included in study. Detail examination and necessary investigations were carried out to diagnose type of skin disease. Results: Out of 131 patients, only 11(8.4%) patients presented with pregnancy specific dermatoses while rest 120 (91.6%) presented with pregnancy non-specific dermatoses. Among pregnancy non-specific dermatoses, non-infectious conditions were found in 48.1% and 43.5% presented with infectious dermatoses. Most common infectious dermatoses was herpes labialis while most common non-infectious dermatosis was pruritus. Conclusions: Pregnancy specific dermatoses are rare and require vigilant eye to recognize them while wide variety of pregnancy non-specific dermatoses are commonly encountered and require prompt diagnosis and treatment for uneventful pregnancy outcome.